African philosophy and deep ecology - Abudu, Kenneth Uyi; Behrens, Kevin Gary; Imafidon, Elvis (Routledge studies in african philosophy, 2026)
"This book investigates African philosophical contributions to the concept of deep ecology, which advocates for rethinking human and non-human relationships within our ecosystems, by promoting the inherent and earned worth of all beings. With ecological crises impacting lives around the world, this book interrogates deep ecology thinking from African philosophical perspectives, highlighting the continent's important ontological, epistemological, ethical, aesthetic, and broad philosophical contributions. The book investigates issues such as the eco-phenomenology of human / non-human animals' relations, Ubuntu and the environment, the superiorist fallacy, environmental belongingness, the impact of colonization and modernity on non-human trauma, the politics of ecological narrative about African places, the question of moral status, African socialist perspectives, the question of degrowth, selective subordination, biodiversity loss, land ethics, the ontology of waste, and the concept of personhood in relation to global climate and ecological justice. Providing a significant intervention in our understanding of the ecological crises and our duties toward ecosystems and the non-human other in the twenty-first century, this book is an important read for researchers, advocates and other stakeholders working in the fields of environmental philosophy, climate change, indigenous studies, and African Studies"-- Provided by publisher